The new HI supershell GS263-02+45 and the OB Association Bochum 7: close relatives? - Corti, Mariela Alejandra (2008)
Neutral hydrogen (HI) supershells are usually identified, in a given velocity range, as a brightness temperature minimum in the HI distribution that is surrounded by walls of HI emission. McClure-Griffiths et al. (2002) reported the discovery of GSH263+00+47, centered at (l,b) = (263°.0, 0°.0). The OB association Bochum 7 (l,b) = (265°.0, -2°.0) is seen in projection onto the outer border of GSH263+00+47 (see Figure 1).